2016
DOI: 10.2298/mpns1608255s
|View full text |Cite
|
Sign up to set email alerts
|

Emergency response teams training in public health crisis: The seriousness of serious games

Abstract: Virtual worlds, which should be the subject of further research and improvements, in the field of hospital emergency response training for mass casualty incidents, certainly have a promising future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[4][5][6] Previous healthcare studies on simulation using mannequins and/or live actors have shown a high acceptance by participants and significant improvement in educational outcomes compared with traditional teaching methods. 7,8 While live exercises are considered the criterion standard for disaster training, they are limited by several factors including high costs, time restraints, and significant resource utilization. 9 A live exercise can take months to prepare, often cannot include large groups, and is difficult to replicate through multiple iterations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Previous healthcare studies on simulation using mannequins and/or live actors have shown a high acceptance by participants and significant improvement in educational outcomes compared with traditional teaching methods. 7,8 While live exercises are considered the criterion standard for disaster training, they are limited by several factors including high costs, time restraints, and significant resource utilization. 9 A live exercise can take months to prepare, often cannot include large groups, and is difficult to replicate through multiple iterations.…”
mentioning
confidence: 99%
“…Beyond this mandate, however, a lack of standardization exists in the education and training of healthcare providers in disaster preparedness 4–6 . Previous healthcare studies on simulation using mannequins and/or live actors have shown a high acceptance by participants and significant improvement in educational outcomes compared with traditional teaching methods 7,8 . While live exercises are considered the criterion standard for disaster training, they are limited by several factors including high costs, time restraints, and significant resource utilization 9 .…”
mentioning
confidence: 99%